Implementasi Program Muhadoroh sebagai Media Pengembangan Public Speaking Santri di Pondok Pesantren Sirojul Haromain Pongangan - Rosiyah Rosiyah; Nur Indah Rofiqoh (SENTRI: Jurnal Riset Ilmiah, 2026)
Public speaking ability is one of the essential communication skills needed by students to support their roles in da’wah, leadership, and social participation. In the context of Islamic boarding schools, this ability is important because students are expected to be able to convey ideas and religious messages clearly and confidently. However, in reality, this ability has not developed optimally among students, including those at Sirojul Haromain Islamic Boarding School, Pongangan. Many students still experience a lack of confidence and difficulty in organizing speech materials. One of the programs organized by the pesantren to develop public speaking skills is the muhadoroh activity, which is conducted regularly as a forum for students to practice speaking in public. This study aims to analyze the implementation of the muhadoroh program as a medium for developing students’ public speaking skills, including planning, implementation, evaluation, and the obstacles encountered. This research employs a qualitative approach using a descriptive method, with data collected through observation, interviews, and documentation. The results indicate that the muhadoroh program plays a positive role in improving students’ self-confidence, speaking courage, and ability to organize presentation materials. Students’ success in the program is assessed through direct feedback from supervisors and administrators after each performance, focusing on criteria such as mastery of material, clarity of delivery, voice intonation, body language, and confidence level. Nevertheless, the effectiveness of the program still faces several challenges, such as limited mentoring, a lack of variation in delivery methods, and unsystematic evaluation. Therefore, strengthening the implementation of the muhadoroh program is necessary to support the more optimal development of students’ public speaking skills.